The politics of justifying force : the Suez crisis, the Iraq War, and international law - Peevers, Charlotte (Oxford : Oxford University Press, 2014)
The potential engagement of British forces in military action often leads to intense public debate. This book assesses the public legal justifications for such operations. It critiques the idea that using international legal norms to justify decisions on the use of force will necessarily result in fewer instances of military intervention.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on December 2, 2013).
Keywords: Intervention (International law); Egypt -- History -- Intervention, 1956.; Iraq War, 2003-2011.